BENEFITING EFL STUDENTS IN LISTENING COMPREHENSION WITH ENGLISH SONGS - Inggar Berlia Sari; Movi Riana Rahmawanti (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to analyse the benefit of listening to English songs to improve their listening skills. This study uses qualitative case study methodology. Qualitative case study methodology enables researchers to conduct an in-depth exploration of complex phenomena within some specific context. According to Baskarada cited in Rashid, case study method is the most widely used in academia for researchers interested in qualitative research. Data collection by giving questionnaires and written interviews in this study were ten students of 4th-semester education class A, English Education Department, one of the private universities in Bogor for the 2020-2021 academic year. This study shows benefits for students in listening to English songs; it can improve English language skills, help students focus more on learning, motivate learning, relax the body, all students agree that listening to English songs can be obtained by listening to English songs as a learning medium. Keywords: song, music, media, learning, learning atmosphere